Site fragmentation, hominin mobility and LCT variability reflected in the early Acheulean record of the Okote Member, at Koobi Fora, Kenya. Issue 125 (December 2018) - Presnyakova, Darya; Braun, David R.; Conard, Nicholas J.; Feibel, Craig; Harris, John W.K.; Pop, Cornel M.; Schlager, Stefan; Archer, Will
Abstract: From its initial appearance at ∼1.7 Ma, the Acheulean was prevalent through a vast chronological span of hominin behavioural evolution that lasted nearly 1.5 million years. The origins and production patterns of large bifacial cutting tools ('LCTs') – the marker of the Acheulean techno-complex – and the systematic changes in this behaviour through time are gaining increasing interest in paleoanthropology. Here we provide a synthesis of early Acheulean LCT variation in a landscape context by analysing assemblages from four different quasi-contemporaneous (∼1.4 Ma) sites from the Koobi Fora Formation. We characterize this variation using both 3D geometric morphometric and descriptive approaches. The expansive lateral exposures of fluvial and lacustrine sediments, as well as the associated tephrostratigraphy of the Koobi Fora Formation provide the landscape context that enables these comparative analyses. Our study demonstrates that when multiple contemporaneous early Acheulean localities are analysed together, a broader picture of LCT variability is elucidated. Four sites at Koobi Fora appear to represent a single system of lithic economy, characterized by a discrete trajectory of changes in LCT size and shape. These sites have ranges of LCT forms which appear to represent different but overlapping stages on a single reduction trajectory. Certain sites exhibit the full reduction trajectory while others exhibit only fragments of this trajectory. Other inter-site lithic proxies further complement these patterns in LCT variability. We explore patterns of site function, mobility and hominin landscape use, all of which may be suggestive of a depth of planning in early Acheulean hominins wherein technological activities were undertaken in substantial anticipation of future needs.